Role of hematological parameters in the selection of acute appendicitis treatment - Goktekin, Mehmet Cagri; Yilmaz, Mustafa; Bozdag, Ahmet (Bayrakol Medical Publisher, 2020)
Aim: The aim of this study was to compare hematological parameters of patients hospitalized and undertaken operative and non-operative antibiotherapy due to acute appendicitis (AA) in the emergency unit, and to investigate its effect on decision-making for the treatment. Materials and Methods: Files of the patients hospitalized in the emergency unit due to AA within two years were obtained from electronic records and were retrospectively evaluated. Patients were grouped according to their treatments as non-operative antibiotherapy and surgical treatment. Hematological parameters of the groups on admission to the emergency unit were compared. Results: Among the 94 patients hospitalized in the emergency unit due to AA and undertaken surgical treatment, 40.4% (n=38) were females and 59.6% (n=56) were males. Among the 108 patients undertaken medical treatment, 38.9% (n=42) were female and 61.2% (n=66) were male. The mean age was 33.4 +/- 14.8 which was similar between groups. Among the hematological parameters compared between antibiotherapy (AT) and surgical treatment (ST) groups, white blood cell (WBC) count (p<0.001), neutrophil count (p<0.01), monocyte count (p=0.010) and neutrophil/lymphocyte ratio (p=0.005) were found to be significantly increased in the surgery group. According to ROC analysis, sensitivity, specificity, positive predictive value (PPV) and negative predictive (NPV) values for WBC count at a cut-off level of >13,3 were 58,51, 65,74, 59,78, and 64,55, respectively. Discussion: WBC, neutrophil and monocyte count, and neutrophil/lymphocyte ratio parameters significantly differed between patients receiving surgical or medical therapy. Conclusion: Hematological parameters may be helpful for the clinician in the selection of the treatment in combination in acute appendicitis, however, they are insufficient alone.
Keywords: Acute Appendicitis; WBC; Neutrophil Count; Monocyte; Neutrophil/Lymphocyte Ratio